Assessing Energy Policies, Legislation and Socio-Economic Impacts in the Quest for Sustainable Development - Eze, Val Hyginus Udoka; Oparaocha, Favour Uzoma; Tamball, John S.; Nakitto, Immaculate Sarah; Oonyu, Robert; Okafor, Wisdom (International Journal of Education, Science, Technology, and Engineering (IJESTE), 2023)
The energy sector in Africa, particularly in countries like Uganda, plays a pivotal role in shaping economic development, social progress, and environmental sustainability. This study delves into the nuanced interplay between energy policies, legislation, and their real-world consequences in Uganda. By employing a case study approach, this research investigates the multifaceted impact of Uganda's energy policies and legislation on various stakeholders, including government institutions, businesses, and local communities. This study provides an overview of Uganda's energy landscape, highlighting the challenges faced by the nation in ensuring a stable and sustainable energy supply. It then meticulously examines the evolution of energy policies and legislation over the past few decades, analysing their formulation, implementation, and effectiveness. Through qualitative and quantitative analyses, this research assesses the socio-economic consequences of these policies and legislations. It explores how regulatory decisions have influenced energy accessibility, affordability, and reliability for urban and rural populations. Additionally, the environmental impact of energy policies is scrutinized, focusing on their contributions to climate change mitigation, natural resource conservation, and the promotion of sustainable practices. The study also evaluates the social repercussions, including the empowerment of local communities, employment generation, and overall improvements in the quality of life resulting from energy policy interventions. This research critically examines the challenges faced during policy implementation, such as bureaucratic hurdles, financial constraints, and political influences, which often hinder the desired outcomes. It identifies key lessons from Uganda's experiences, offering valuable insights for other African nations grappling with similar energy challenges.